Flashback: Politics - Språkbanken Text (University of Gothenburg, 2014)
Material from the Flashback internet forum.

Material från diskussionsforumet Flashback.
Flashback: Politik
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik